Improved process for sweet potato chip production - Ong, Christabel Gahn C.; Acevedo, Teresita P. (1996.)
An existing process for the production of sweet potato chips was modified to be able to achieve a final product which closely resembles commercially sold potato chips in terms of appearance and texture. After modifications were made on the thickness of the slices and the blanching method and duration, adjustments were also done on the time and temperature of frying. The modified process was subsequently standardized. Sweet potato chips were made using the standardized process were added with five different types of flavoring -- Nacho Cheese, Sour Cream and Onion, Ethnic Spice, Chicken barbecue and Plain Salt. Each type of flavored chip was subjected to sensory evaluation. Based on the sensory test results, the best and least preferred flavor were determined. The product from the modified process was further subjected to proximate analysis. Sensory results revealed that the product from the modified process was more acceptable compared to those from basic process. Modifications made on this new process included a reduction in the thickness of the slices to 1.5mm and a subsequent change in the blanching method from steam blanching to water blanching. The frying time temperature was changed to 4 minutes at 150°C. Sensory results on the evaluation of the flavored chips further showed that Sour Cream and Onion was most preferred among the five flavors, being followed by the Chicken Barbecue flavor.
Thesis (BSFT)--University of the Philippines Diliman.
Keywords: Potato chips